An alternative stability proof for robust control of electrically driven robots using adaptive uncertainty estimation. (September 2019) - Izadbakhsh, Alireza; khorashadizadeh, Saeed
Highlights: The objective of this paper is to modify the previous results on the robust stability analysis of the work proposed by [1]. We focus on the convergence of main signals and boundedness of other signal in MIMO form subjected to actuator voltage input constraint. The overall closed-loop system composed by full actuated robotic manipulator for n degrees of freedom and the proposed controller is proved to be stable, while the joint position and velocity tracking errors are Uniformly-Ultimately Bounded (UUB) stable in agreement with Lyapunov's direct method in any finite region of the state space. Abstract: This paper points out an improvement on the robust stability analysis for electrically driven robots given in the paper "robust control of electrically driven robots using adaptive uncertainty estimation". In the aforementioned paper, a robust adaptive control scheme for electrically driven robots has been presented. The uncertainties have been estimated and compensated using Taylor series expansion. The nonlinearities associated with actuator input constraints have been considered in that paper. It discussed the saturated and unsaturated region of the control input separately and neglected the transition state between these regions. Moreover, it did not guarantee the stability of the closed-loop system in the saturated area. In this paper, an alternative stability proof is presented that do not require this separation and guarantee the stability in a more general framework. Moreover, in the performance evaluation, the upper bound for the error vector of Taylor series coefficients estimations is calculated.